EVALUATION OF THE PERFORMANCE OF THE AQUACROP MODEL UNDER DIFFRENT IRRIGATION AND CULTIVATION METHODS AND THAIR EFFECT ON WATER CONSUMPTION. - D. F. Hassan,; A. S. Ati,; A. S. Naima, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to evaluate the Aqua program in calibration and validity and its use in simulation to study the productive and water characteristics of maize crop.. The experiment was conducted in two irrigation methods, sprinkler irrigation and surface irrigation, and two cultivation methods are borders (lines) and furrows (lines and then furrows) and for two cultivars of maize, a hybrid (unlocal) and a local variety. The results that sprinkler irrigation reduced water consumption compared to surface irrigation, as it reached (558.38) mm for sprinkler irrigation, and (668.79) mm for surface irrigation. While the method of furrows after borders outperformed the borders only in improving growth characteristics and increasing productivity, and the hybrid (unlocal) cultivar outperformed the local cultivar. The various experimental parameters were also calibrated using Aquacrop program, and it was found that the program gave a good convergence between the simulated and field values, as it gave R2 values that ranged between (0.71-0.92) and RMSE between (0.12-23.76) for all studied traits.